Bacterial delivery of therapeutic proteins to the nuclei of cancer cells. Issue 5 (12th February 2023) - Bloom, Shoshana M. K.; O'Hare, Nicholas; Forbes, Neil S.
Abstract: Targeting nucleic targets with therapeutic proteins would enhance the treatment of hard‐to‐treat cancers. However, exogenous proteins are excluded from the nucleus by both the cellular and nuclear membranes. We have recently developed Salmonella that deliver active proteins into the cytoplasm of cancer cells. Here, we hypothesized that bacterially delivered proteins accumulate within nuclei, nuclear localization sequences (NLSs) increase delivery, and bacterially delivered proteins kill cancer cells. To test this hypothesis, we developed intranuclear delivering (IND) Salmonella and quantified the delivery of three model proteins. IND Salmonella delivered both ovalbumin and green fluorescent protein to nuclei of MCF7 cancer cells. The amount of protein in nuclei was linearly dependent on the amount delivered to the cytoplasm. The addition of a NLSs increased both the amount of protein in each nucleus and the number of nuclei that received protein. Delivery of Omomyc, a protein inhibitor of the nuclear transcript factor, Myc, altered cell physiology, and significantly induced cell death. These results show that IND Salmonella deliver functional proteins to the nucleus of cancerous cells. Extending this method to other transcription factors will increase the number of accessible targets for cancer therapy.